ChemInform Abstract: Alcoholic Solvent‐Assisted Ligand‐Free Room Temperature Suzuki—Miyaura Cross‐Coupling Reaction. Issue 52 (10th December 2015) - Sarmah, Gayatri; Mondal, Manoj; Bora, Utpal
Abstract: The in situ generated active Pd(0) species is responsible for the excellent catalytic activity.